Summon the bright water - Household, Geoffrey, 1900- (Little, Brown, 1981)
Piers Colet, a British economic historian, investigates a cult of druidical devotees and their leader, the charismatic Simeon Marrin, with the help of Marrin's beautiful niece Elsa and the eccentric Major Matravers-Drummond [By Publisher]